Invasive Dental Treatment and Risk for a First Myocardial Infarction. (September 2018) - Nordendahl, E.; Kjellström, B.; Fored, C.M.; Ekbom, A.; Svensson, T.; Norhammar, A.; Gustafsson, A.
Invasive dental treatment is suggested to be associated with an increased risk for the development of cardiovascular events. We tested the hypothesis that the incidence of a first myocardial infarction (MI) within 4 wk after invasive dental treatments is increased. A registry-based case-control study within nationwide health care and population registries in Sweden was performed. The case patients included 51, 880 individuals with a first fatal or nonfatal MI between January 2011 and December 2013. For each case, 5 control subjects, free from prior MI and matched for age, sex, and geographic area of residence, were randomly selected from the national population registry through risk set sampling with replacement, resulting in 246, 978 control subjects. Information on dental treatments was obtained from the Dental Health Register, and the procedures were categorized into invasive dental treatments or other dental treatments. Conditional logistic regression was used to estimate odds ratios (ORs) for MI with corresponding 95% confidence intervals (CIs). In addition to the matching variables, adjustments were made for the following confounders: diabetes, previous cardiovascular disease (CVD), CVD drug treatment, education, and income. The mean age for case patients and controls subjects was 72.6 ± 13.0 y and 72.3 ± 13.0 y, respectively. Case patients more often had previous CVD (49% vs. 23%; P < 0.001) and diabetes (19% vs. 11%; P < 0.001) and received more treatment with CVD drugs (68% vs. 56%; P < 0.001) than control subjects. There was no association between invasive dental treatments during the 4 wk preceding the MI index date (crude OR = 0.99; 95% CI, 0.92 to 1.06; adjusted for confounders OR = 0.98; 95% CI, 0.91 to 1.06). This study did not support the hypothesis of an increased incidence of MI after recent invasive dental treatment.